(untitled) (Cardiovascular Journal, 2023)
Background: Sodium and potassium intake is known to be a modifiable determinant of hypertension. Also, daily intake of these electrolytes is subject to much geographical and ethnic variation. The impact of sodium and potassium intake on blood pressure in Bangladeshi subjects in incompletely known. Our objective was to determine the relationship between urinary sodium and potassium excretion, and blood pressure in Bangladeshi subjects. Methods: Patients attending the Outpatient Department of the Department of Cardiology, SSMC & MH, who fulfilled the inclusion and exclusion criteria, were taken as study sample. Hypertensive individuals were considered as group 1 and apparently healthy individuals who did not have hypertension were considered as group 2 for the study. Estimates of 24-hour sodium and potassium excretion were made from a single spot urine specimen and were used as surrogates for intake. We assessed the relationship between sodium and potassium excretion and blood pressure. Results: The spot urinary sodium excretion was significantly higher in hypertensive group than in normotensive group (98.03 ± 71.13 mmol/L vs. 77.11 ± 41.71 mmol/L) (p=0.011). On the other hand, the spot urinary potassium excretion was lower in hypertensive group than normotensive group (33.95 ± 41.03 mmol/L vs. 39.43 ± 31.47 mmol/L), but the differences did not reach statistical significance (p=0.679). The estimated 24-hour urinary sodium excretion was higher in hypertensive group than in normotensive group (8.84 ± 3.57 gm vs. 7.67 ± 3.16 gm) and the difference was statistically significant (p = 0.015). Estimated 24-hour urinary potassium excretion was lower in hypertensive group (4.15 ± 1.37 gm) than in normotensive group (4.48 ± 1.56 gm), but the difference between 2 values did not reach statistical significance (p=0.114). Conclusion: Compared to the normotensive counterparts, sodium intake is significantly higher and potassium intake is lower in hypertensive Bangladeshi subjects. Cardiovasc j 2023; 15(2): 118-123